PENGARUH PENYULUHAN KESEHATAN TERHADAP PENGETAHUAN IBU HAMIL TENTANG PENCEGAHAN ANEMIA DI PURI CLINIC KOTA PEKANBARU - Shintya Adella; Fajar Sari Tanberika; Meirita Herawati; Rizka Mardiya (Ensiklopedia Research and Community Service Review, 2026)
Anemia in pregnant women remains a public health problem that can cause adverse effects on both the mother and the fetus. One of the efforts to prevent anemia is through improving pregnant women’s knowledge by providing health education. This study aimed to determine the effect of health education on pregnant women’s knowledge regarding anemia prevention at Puri Clinic, Pekanbaru City. This research employed a pre-experimental design with a one-group pre-test–post-test approach. The sample consisted of 15 pregnant women selected using total sampling technique. The research instrument was a questionnaire measuring knowledge of anemia prevention. Data analysis was conducted using univariate and bivariate analysis with the Paired Sample t-Test. The results showed that the mean knowledge score of pregnant women before health education was 59.53 with a standard deviation of 22.34, a minimum score of 23, and a maximum score of 85. After health education, the mean knowledge score increased to 84.13 with a standard deviation of 12.77, a minimum score of 54, and a maximum score of 100. Statistical analysis revealed a p-value of 0.000 (p 0.05), indicating a significant effect of health education on pregnant women’s knowledge of anemia prevention. In conclusion, health education has a significant effect on improving pregnant women’s knowledge regarding anemia prevention at Puri Clinic, Pekanbaru City.Keywords: Health education, knowledge, anemia, pregnant women